Quantifying greenhouse gas emissions reduction from bike share systems: A model considering real-world trips and transportation mode choice patterns - Kou, Zhaoyu (Animo Repository, 2020)
The emerging bike share systems provide convenient mobility to short-distance travelers for both leisure and commuting purposes. Many cities are rolling out bike share programs. However, few studies have evaluated how bike share systems (BSS) are used to quantify their sustainability impacts. This study proposes a Bike Share Emission Reduction Estimation Model (BS-EREM) to quantify the environmental benefits from bike share trips and compare the greenhouse gas (GHG) emission reductions from BSS in eight cities in the United States, including New York, Chicago, Boston, Philadelphia, Washington D.C., Los Angeles, San Francisco, and Seattle. The BS-EREM model stochastically estimates the transportation modes substituted by bike share trips, considering factors such as trip distance, trip purpose, trip start time, the accessibility of public transits, and historical distributions of transportation mode choices. Based on average life cycle emission factors of different transportation modes, our analysis reveals that the annual GHG emission reductions contributed by the eight BSSs in year 2016 range from 41 tons of CO2-eq (Seattle) to 5417 tons of CO2-eq (New York City), while the emission reductions per trip range from 283 to 581 g CO2-eq. The total annual emission reduction is linearly correlated to the number of trips, bikes, and docks. The bike share stations located in the center of a city contributed to more total GHG emission reductions due to the high trip volumes, while the stations that are further away have higher emission reductions on a per trip basis due to longer trips and higher car substitution rate. © 2019 Elsevier B.V.